Bioorthogonal regulation of DNA circuits for smart intracellular microRNA imaging. Issue 47 (24th November 2021) - Chen, Yingying; Gong, Xue; Gao, Yuhui; Shang, Yu; Shang, Jinhua; Yu, Shanshan; Li, Ruomeng; He, Shizhen; Liu, Xiaoqing; Wang, Fuan
Abstract : An on-site bioorthogonal regulated DNA circuit was developed by introducing an endogenous DNA repairing enzyme-mediated sequential activation strategy to achieve cancer cell-selective microRNA imaging with high anti-interference ability. Abstract : Catalytic DNA circuits represent a versatile toolbox for tracking intracellular biomarkers yet are constrained with low anti-interference capacity originating from their severe off-site activation. Herein, by introducing an unprecedented endogenous DNA repairing enzyme-powered pre-selection strategy, we develop a sequential and specific on-site activated catalytic DNA circuit for achieving the cancer cell-selective imaging of microRNA with high anti-interference capacity. Initially, the circuitry reactant is firmly caged by an elongated stabilizing duplex segment with a recognition/cleavage site of a cell-specific DNA repairing enzyme, which can prevent undesired signal leakage prior to its exposure to target cells. Then, the intrinsic DNA repairing enzyme of target cells can liberate the DNA probe for efficient intracellular microRNA imaging via the multiply guaranteed molecular recognition/activation procedures. This bioorthogonal regulated DNA circuit presents a modular and programmable amplification strategy for highly reliable assays of intracellular biomarkers, and provides a pivotal molecular toolbox for living systems.